2020
DOI: 10.1080/17480272.2020.1804996
|View full text |Cite
|
Sign up to set email alerts
|

The effect of class-balance and class-overlap in the training set for multivariate and product-adapted grading of Scots pine sawn timber

Abstract: Using multivariate partial least squares regression (PLS) to perform visual quality grading of sawn timber requires a training set with known quality grades for the training of a grading model. This study evaluated the grading accuracy of an independent test set of sawn timber when changing the aspects of classbalance and class-overlap of the training set consisting of 251 planks. The study also compared two ways of expressing the reference-grade of the training set; by grading images picturing the planks, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…However, the percentage of rejection depends on the strength class combination considered, being the maximum increment of percentage of rejection (16%) reached for Scots pine in the combination C24/C18. For all the cases, it was observed that combinations with strength classes close to each other resulted in lower yields of the lower strength class and higher percentage of rejections, in agreement with that Olofsson et al [27] reached for Scots pine in Sweden. For example, for maritime pine, the yield of the strength class combination C27/C16/R resulted in values of 42%/57%/1% for in-line grading while the yield for C24/C16/R resulted in values of 64%/20%/16%; that is, a decrease of 22% of the yield of the second strength class and an increase of 15% of rejected specimens.…”
Section: Machine Gradingsupporting
confidence: 89%
“…However, the percentage of rejection depends on the strength class combination considered, being the maximum increment of percentage of rejection (16%) reached for Scots pine in the combination C24/C18. For all the cases, it was observed that combinations with strength classes close to each other resulted in lower yields of the lower strength class and higher percentage of rejections, in agreement with that Olofsson et al [27] reached for Scots pine in Sweden. For example, for maritime pine, the yield of the strength class combination C27/C16/R resulted in values of 42%/57%/1% for in-line grading while the yield for C24/C16/R resulted in values of 64%/20%/16%; that is, a decrease of 22% of the yield of the second strength class and an increase of 15% of rejected specimens.…”
Section: Machine Gradingsupporting
confidence: 89%